Exploring the Role of Information Technology in Modern Security and Crime Detection Systems - Mohmad Nawid Hasan Zada; Nasrullah Rahimi; Hamidullah Akhlaqi; Hafizullah Mohammadi (Gameology and Multimedia Expert, 2026)
In the modern and digital world, information technology (IT) has become an essential pillar in maintaining security and fighting crime. With the rapid development of modern technologies such as artificial intelligence, big data analytics, smart surveillance systems and digital forensic software, traditional security approaches are no longer sufficient to address today’s complex challenges. This study examines the role and impact of IT in enhancing the performance of security institutions, improving crime detection and prediction capabilities, and enhancing the sense of public security. This research focuses mainly on the questionnaire survey in Afghanistan and provides practical examples and comparative analyses to provide strategies for better integration of IT into national security systems. Findings based on scientific research and field data show that the effective use of IT significantly increases response time, accuracy in evidence analysis, and reduces crime rates. However, this evolution requires careful management, privacy protection, and human capacity development in technology-related sectors. As a result, integrating IT into the security sector is not only a technical necessity, but also a strategic imperative for countries like Afghanistan. With appropriate investment, training, and policy development, IT can serve as a powerful tool for creating a safer and more resilient society.